2016
DOI: 10.1155/2016/2867470
|View full text |Cite
|
Sign up to set email alerts
|

Potential Benefits of Jujube (Zizyphus Lotus L.) Bioactive Compounds for Nutrition and Health

Abstract: Zizyphus lotus, belonging to the Rhamnaceae family, is a deciduous shrub which generally grows in arid and semiarid regions of the globe. In traditional medicine, Z. lotus is used as antidiabetes, sedative, bronchitis, and antidiarrhea by local populations. Recently, several scientific reports for health benefit and nutritional potential of bioactive compounds from this jujube have been reported. This plant is rich in polyphenols, cyclopeptide alkaloids, dammarane saponins, vitamins, minerals, amino acids, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 70 publications
4
51
5
Order By: Relevance
“…Regarding the content of the glycosides triterpenoids, R. tripartita showed the highest amount (12 mg/g DW), while in the other plant leaf extracts, the amount of saponins ranged between 0.3% and 0.9%, with a high sampling variance σ 2 of 0.09. The saponin content measured in Z. lotus (0.9%) was more than double the amount (0.4%) found by Abdoul-Azize [39], while in P. ovata , the concentration of these compounds (0.8%) was in line with that observed by Mamta [46] which measured a content of 0.7% in the leaves.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding the content of the glycosides triterpenoids, R. tripartita showed the highest amount (12 mg/g DW), while in the other plant leaf extracts, the amount of saponins ranged between 0.3% and 0.9%, with a high sampling variance σ 2 of 0.09. The saponin content measured in Z. lotus (0.9%) was more than double the amount (0.4%) found by Abdoul-Azize [39], while in P. ovata , the concentration of these compounds (0.8%) was in line with that observed by Mamta [46] which measured a content of 0.7% in the leaves.…”
Section: Resultssupporting
confidence: 85%
“…There are not many data available in literature about the plants examined in this study, so making a comparison of the results we obtained is not easy. Nonetheless, a few papers reported the amount of phenolics in some of these plants; recently, in a review about the biochemical composition of different parts of Z. lotus , Abdoul-Azize [39] reported around 7 mg/g of phenolics to be present in the leaves, almost 5 times less than the amount measured in our study. Moreover, in the same review, the tannin content observed in the leaves was the same that we measured in the samples described in this paper (around 3.0 mg/g).…”
Section: Resultscontrasting
confidence: 79%
“…This difference might occur even for the same variety of Zizyphus, which is mainly due to the extraction, the purification and the separation conditions [19]. Z. lotus fruit has considerable amounts of sugars [2]. Sucrose was the most abundant in Z. lotus fruit, it was reported that other monosaccharides are frequently detected in Z. lotus fruit species, such as arabinose, galactose and rhamnose [19].…”
Section: Jujube Powder Characteristics: Chemical and Functional Charamentioning
confidence: 99%
“…This plant is used in nutrition, health, and cosmetics in various forms (honey, juice, tea, jam, loaf, oil and cake). Besides, this plant presents a delicious red fruit (jujube) that is consumed freshly, dried and processed into flour to make pancakes with very pleasant flavor by local population [2]. The Z. lotus fruit is used also in folk medicine for the treatment of several illness, such as bronchitis, diabetes, diarrhoea, intestinal diseases and abscess [3].…”
Section: Introductionmentioning
confidence: 99%
“…e jujube (Ziziphus lotus L.), commonly called "Sedra" in Morocco, as a local product targeted by this study, grows on all the southern shores of the Mediterranean [11]. As traditional medicinal plants, it is recommended for digestive disorders, weakness, liver diseases, obesity, urinary disorders, diabetes, skin infections, fever, diarrhea, and insomnia [12][13][14]. Other Ziziphus fruits effects have been reported as antiaging, antitumoral, anti-inflammatory, antiulcerogenic, and antibacterial [15,16].…”
Section: Introductionmentioning
confidence: 99%